From Outbreak to Near Disappearance: How Did Non-pharmaceutical Interventions Against COVID-19 Affect the Transmission of Influenza Virus? - Song, Shuxuan; Li, Qian; Shen, Li; Sun, Minghao; Yang, Zurong; Wang, Nuoya; Liu, Jifeng; Liu, Kun; Shao, Zhongjun (Frontiers in Public Health, 2022)
Influenza shares the same putative transmission pathway with coronavirus disease 2019 (COVID-19), and causes tremendous morbidity and mortality annually globally. Since the transmission of COVID-19 in China, a series of non-pharmaceutical interventions (NPIs) against to the disease have been implemented to contain its transmission. Based on the surveillance data of influenza, Search Engine Index, and meteorological factors from 2011 to 2021 in Xi’an, and the different level of emergence responses for COVID-19 from 2020 to 2021, Bayesian Structural Time Series model and interrupted time series analysis were applied to quantitatively assess the impact of NPIs in sequent phases with different intensities, and to estimate the reduction of influenza infections. From 2011 to 2021, a total of 196,542 influenza likely illness cases were reported in Xi’an, and the incidence of influenza continuously increased from 2011 to 2019, especially, in 2018-2019, when the incidence was up to 61.99 per 100,000 persons; however, it showed a sharp reduction of 98.18% in 2020, and of 87.66% in 2021, comparing with 2018-2019. The highest impact on reduction of influenza was observed in the phase of strict implementation of NPIs with an inclusion probability of 0.54. The weekly influenza incidence was reduced by 95.45%, and an approximate reduction of 210,100 (95%CI: 125,100-329,500) influenza infections was found during the post-COVID-19 period. The reduction exhibited significant variations in the geographical, population, and temporal distribution. Our findings demonstrated that NPIs against COVID-19 had a long-term impact on the reduction of influenza transmission.